Multiphase Approach to Developing Model of Logistics for Coastal Tourist Destinations - Ivanović, Željko; Bauk, Sanja (Promet - Traffic&Transportation, 2014)
The process of urbanization of coastal tourist destinations (CTDs) is taking place at high speed and at the same time creating a lot of complex problems. The positive trend of urbanization has resulted in increased volume of freight transport which leads to burdening the traffic network, time losses and causes traffic congestion problems on the streets with increased environmental pollution due to emissions, noise and vibration. These findings brought to some research being started on the EU level, aiming to develop new logistic solutions, so these areas could be developed on a sustainable basis. With this in mind, the paper proposes a method of developing a novel model of logistics (MoL) for CTDs through several stages. The point of proposed MoL lies in achieving optimal connectivity of transportation, warehousing and physical distribution of goods, and making it a single functional model, so as to allow simultaneous optimization of logistic processes in a CTD, and to incorporate logistics in tourist offer.